2019
DOI: 10.1103/physrevb.99.134411
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting spin-flop coupling and exchange bias in LaFeO3/La0.7Sr0.3

Abstract: Exchange bias occurs in field-cooled antiferromagnet/ferromagnet systems and can most often be explained in terms of uncompensated magnetic moments at the interface, that are pinned in their orientation during field-cooling. The presence of spin-flop coupling is often associated with spincompensated interfaces. Here, we report exchange bias in complex oxide heterostructures of antiferromagnetic LaFeO 3 and thin layers of ferromagnetic La 0.7 Sr 0.3 MnO 3 with several intriguing features. The exchange bias does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For a fully compensated antiferromagnetic surface, such as the (001) plane of a G-type antiferromagnet, a spin-flop coupling is energetically favorable [7]. The antiferromagnetic spin axis aligns perpendicular to the ferromagnetic spins to minimize the interfacial spin frustration, as revealed at La 0.7 Sr 0.3 MnO 3 /La(Sr)FeO 3 interfaces [8][9][10]. Normally such spin-flop coupling is unable to induce EB, but only increases H C , while extrinsic disorders (interface roughness, for example) can create random fields acting on the ferromagnetic spins and cause EB [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a fully compensated antiferromagnetic surface, such as the (001) plane of a G-type antiferromagnet, a spin-flop coupling is energetically favorable [7]. The antiferromagnetic spin axis aligns perpendicular to the ferromagnetic spins to minimize the interfacial spin frustration, as revealed at La 0.7 Sr 0.3 MnO 3 /La(Sr)FeO 3 interfaces [8][9][10]. Normally such spin-flop coupling is unable to induce EB, but only increases H C , while extrinsic disorders (interface roughness, for example) can create random fields acting on the ferromagnetic spins and cause EB [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Normally such spin-flop coupling is unable to induce EB, but only increases H C , while extrinsic disorders (interface roughness, for example) can create random fields acting on the ferromagnetic spins and cause EB [11,12]. Also, an intrinsic mechanism involving Dzyaloshinskii-Moriya interaction has been proposed to explain the EB at ferromagnetic/G-type antiferromagnetic interface [10,13]. In particular, it has been reported that the orbital hybridization and superexchange interaction between Mn and Fe at the interface of La 2/3 Sr 1/ 3 MnO 3 /BiFeO 3 gave rise to a spin-canted state of Fe 3+ and a concomitant EB effect [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These uncompensated arrangement of spins at the LFO (111) p /CFO (111) interface enables EB by pinning the spins in the CFO, resulting in a net negative EB. However, we cannot exclude the possibility of other mechanisms such as Dzyaloshinskii–Moriya interaction (DMI)-driven exchange coupling , simultaneously existing at compensated facets of LFO.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Exchange bias has been studied in oxide–oxide systems such as layered structures of BiFeO 3 –La 0.7 Sr 0.3 MnO 3 or LaFeO 3 –La 0.7 Sr 0.3 MnO 3 , self-assembled nanocomposites of BiFeO 3 –La 0.7 Sr 0.3 MnO 3 , BiFeO 3 –Fe 3 O 4 , or NiO–NiFe 2 O 4 , or even within a single-phase La 0.67 Sr 0.33 MnO 3 or YFeO 3 that exhibit structural variations. In particular, for vertical self-assembled nanocomposites, an exchange bias of ∼100 mT in a 1 μm thick BiFeO 3 –La 0.7 Sr 0.3 MnO 3 at 5 K, ∼4 mT in 250 nm thick BiFeO 3 –Fe 3 O 4 at room temperature, and ∼91 mT in 180 nm thick NiO–NiFe 2 O 4 at room temperature have been reported. Orthoferrites (perovskite-structured RFeO 3 , R: rare earth, Y) are especially attractive antiferromagnets due to their high Néel temperatures of ∼650 K and their compatibility in forming self-assembled nanocomposites with spinels.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of a fully compensated AFM surface, where the AFM spins align themselves perpendicular to the FM spins to minimize the interfacial spin frustration, this resulted in a spin-flop coupling, which in return enhanced H C without inducing an EB. The investigation by Vafaee et al [ 32 ] into La 0.7 Sr 0.3 MnO 3 /BiFeO 3 (LSMO/BFO) heterostructures revealed the absence of an EB coupling for multistacks with a sharp interface, whereas a sizable EB coupling was observed for (LSMO/BFO) heterostructures with rough and chemically mixed interfaces [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Furthermore, the structural misfit at the heterointerfaces in other types of multifunctional heterostructures (e.g., BaFe 12 O 19 /BaTiO 3 [ 9 ], La 0.7 Sr 0.3 MnO 3 /BiFeO 3 [ 32 ], LaMnO 3 /LaFeO 3 [ 33 ], LaMnO 3 /LaNiO 3 [ 48 ]) was tuned by the material combination as well as by the growth sequence with the goal to modify the exchange interaction [ 9 , 32 , 33 , 48 ].…”
Section: Introductionmentioning
confidence: 99%